2021
DOI: 10.1097/bot.0000000000001952
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Frailty and Malnutrition on Outcomes After Surgical Fixation of Lower Extremity Fractures in Young Patients

Abstract: Objectives: Evaluate the relationship of nutrition parameters and the modified frailty index (mFI) on postsurgical complications within a young patient population sustaining lower extremity orthopaedic trauma. Design: Retrospective observational cohort study. Setting: Urban, American College of Surgeons-Verified, Level-1, Trauma Center. Patients/Participants: Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“… 13 In addition to these variables, hypoalbuminemia is an important predictor of outcomes after orthopaedic surgery, although it is not routinely measured in clinical care nor included in frailty indices. 27 28 29 30 31 In this study, hypoalbuminemia was considered in addition to the five items of the MF-5 to create a six-item modified frailty index (MF-6). The purpose of this study was to assess the use of the MF-6 in predicting short-term (≤30 days) adverse outcomes among patients older than 65 years undergoing open reduction and internal fixation for lower extremity, pelvic, and acetabular fractures in the inpatient setting.…”
mentioning
confidence: 99%
“… 13 In addition to these variables, hypoalbuminemia is an important predictor of outcomes after orthopaedic surgery, although it is not routinely measured in clinical care nor included in frailty indices. 27 28 29 30 31 In this study, hypoalbuminemia was considered in addition to the five items of the MF-5 to create a six-item modified frailty index (MF-6). The purpose of this study was to assess the use of the MF-6 in predicting short-term (≤30 days) adverse outcomes among patients older than 65 years undergoing open reduction and internal fixation for lower extremity, pelvic, and acetabular fractures in the inpatient setting.…”
mentioning
confidence: 99%
“…In the last few years, several studies have demonstrated the capacity of frailty scores and markers to predict postoperative outcomes [37,38]. Frailty and malnourishment have demonstrated a synergistic effect when compared with malnourishment alone in predicting the potential for postoperative complications [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several studies have demonstrated the capacity of frailty scores and markers to predict postoperative outcomes [37,38]. Frailty and malnourishment have demonstrated a synergistic effect when compared with malnourishment alone in predicting the potential for postoperative complications [38]. Frailty has also been shown to increase the risk of postoperative morbidity, even when controlling for other comorbidities, and demographic factors [37].…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic locations were grouped by CPT code into procedures of the femur (27470 and 27472) or tibia and fibula (27720, 27722, 27724, 27725, and 27726), as is consistent with previous studies. 28–30…”
Section: Methodsmentioning
confidence: 99%
“…The anatomic locations were grouped by CPT code into procedures of the femur (27470 and 27472) or tibia and fibula (27720, 27722, 27724, 27725, and 27726), as is consistent with previous studies. [28][29][30] Preoperative Variables Demographic data collected included age, sex, race, and ASA class, as well as comorbidities including smoking, dialysis, bleeding disorders, obesity, and chronic steroid use. To allow for multivariate regression analysis of postoperative outcomes, patients were excluded if they were missing any of the demographic variables which were entered as inputs in the regression model.…”
Section: Lower Extremitymentioning
confidence: 99%